The uncertainty of the effect of digital imaging spectral functionals of the image - Hegedűs, Héza; Horváth, Zoltán (Acta Agraria Kaposváriensis, 2011)
Objects - these are in the agriculture mostly plants - are numbers being available to their digital images with different definitions. Some examinationsare converging to identification subjects with selection appropiate definitions, or characterization of its properties. In this text we analyze the following functionals: Spectral fractal dimension (SFD), Spectral moment of inertia (STN), Spectral convex hull Reduced Rate (RSKBM), and then compares these vector value a service function, the two-spectral-norm distance (ST2). We will inspect that how are influencing the conditions of image acquisition the values of certain functions, the results are showing what kind of distribution, and the measurement disposes what kind of error. Furthermore it will be manifested numeracy needs of some processes. I will be demonstrated (with random two examples) the extent of the measurement results can be used to separate plants. We examine the question of whether it is worth to strip the visual information to a scalar if often its numeracy needs are questionable their practical usability, rather than it is available results including complex more informations with much less counting.